Failure Mechanism and Mechanical Properties of a Retard-Bonded Prestressed Concrete Girder While Curing - Wei-ning Sui; Zi-yi Wang; Zhong-hua Zhao; Zhan-fei Wang (Advances in Civil Engineering)
The mechanical performance and failure mechanism of a retard-bonded (RB) type prestressed concrete (PC) girder in different curing periods are investigated through four-point loading experiments. Six RB-type PC girder specimens with three RB prestressed tendons (PTs) along the longitudinal direction were fabricated. The measurements include the following: the retard-bonded agent ages versus the load-carrying capacity of the girder, the deflection of girder, the strain distribution at key cross sections through the girder, the pressure at PT tensile and anchoring ends, crack distribution, and so on. The experimental results indicate that when stretching the PT within proper tensile period, the retarder curing ages have less impact on the cracking load and a greater impact on the ultimate bending strength; the ultimate bending strength of the RB-type PC girder increased with increased retarder curing. Nonetheless, stretching the PT after excessive retarder curing (after the retarder had solidified completely), the cracks in the PC girder’s pure bending segment are wider and less numerous, the ultimate bending strength of the girder is lower, and its ductility is poor.